Merajut Kebersamaan: Pendekatan Praktis Resolusi Konflik Karyawan di UPT Asrama Haji Lombok - Ardi; Suprapto; Abdul Malik (Institut Pendidikan Alfatah Mataram, 2025)
Conflict management theory states that conflict in organizations can arise due to individual differences and structural changes. This research aims to identify the causes of employee conflict at the Lombok Embarkation Hajj Dormitory UPT, analyze effective resolution strategies, and evaluate its impact on organizational performance. This research methodology uses a qualitative approach with in-depth interview techniques and direct observation of employees at UPT Asrama Haji Lombok. The research results show that conflict in the workplace is triggered by differences in backgrounds, values, experiences and communication styles between employees, as well as organizational changes and changes in leadership. Well-managed conflict can be an opportunity for improvement, increasing creativity, motivation and productivity. Effective conflict resolution strategies include open communication and empathy, a collaborative approach, mediation by a third party, a systemic approach, and conflict management training. The negative impacts of conflict that are not well managed include reduced productivity, decreased morale and job satisfaction, and increased employee turnover. Conversely, if conflict is managed constructively, it can encourage innovation, increase collaboration, and strengthen decision making and leadership in the organization.